The relationship between knowledge management and creativity in bachelor degree compared to master degree nursing students - Tehranineshat, Banafsheh; Rakhshan, Mahnaz (Investigación y Educación en Enfermería, 2018)
Objective To investigate the relationship between knowledge management and creativity in undergraduate compared with master degree nursing students. Methods This cross-sectional study was conducted with nursing students of the faculty of nursing and midwifery in an urban area in the southeast of Iran from August 2017 to January 2018. In this study, 180 students were selected using a simple random sampling method (Bachelor degree=120 and Master degree=60). Data was collected using the Nonaka and Takeuchi̛s knowledge management and Randsip’s Creativity questionnaires. Results There was a direct and significant relationship between knowledge management and creativity in the students (r=0.47 in Bachelor degree and r=0.36 in Master degree). The mean scores of knowledge management dimensions and creativity were higher in the master degree students. Conclusion. There was a relationship between knowledge management and creativity in the bachelor and master degree students. It is necessary to corroborate the Efforts for the implementation of strategies for the knowledge management in all its dimensions. Therefore, the education environment can help with the development of students’ knowledge and skills. How to cite this article: Tehranineshat B, Rakhshan M. The relationship between knowledge management and creativity in bachelor degree compared to master degree nursing students. Invest. Educ. Enferm. 2018; 36(3):e05.